2012
DOI: 10.1186/1472-6831-12-35
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and ability to pay for unexpected dental expenses by Finnish adults

Abstract: BackgroundSince 2002, adults have been able to choose oral health care services in the public sector or in the private sector in Finland. Though various subsidies for care exist in both sectors, the Public Dental Service (PDS) is a cheaper option for the patient but, on the other hand, there are no waiting lists for private care. The aim of this study was to assess middle-aged adults' use of dental services, willingness to pay (WTP) and ability to pay (ATP) for unexpected, urgent dental treatment.MethodsPostal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 8 publications
3
34
0
3
Order By: Relevance
“…Firstly, about 80% of dentists are working in private sector [14] and dental services are generally provided with high copayments by users. Since people with higher SR have higher capacity to pay and/or higher knowledge about the importance of oral health, then they have potentially higher demand for dental services than their counterpart with poor SR [37,38,39]. Secondly, as it was shown by a recent study in Iran [40], better employment and social opportunities are determinant factors in decision-making for their career among dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, about 80% of dentists are working in private sector [14] and dental services are generally provided with high copayments by users. Since people with higher SR have higher capacity to pay and/or higher knowledge about the importance of oral health, then they have potentially higher demand for dental services than their counterpart with poor SR [37,38,39]. Secondly, as it was shown by a recent study in Iran [40], better employment and social opportunities are determinant factors in decision-making for their career among dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Private dentists regularly recall most of their patients [20] and a recent questionnaire study of middle aged Finnish adults living in the Helsinki metropolitan region in 2007 showed that slightly fewer than half of them would have been able to pay for private care. The same study also showed that only 9.2% of the respondents had used both sectors [21]. Our results are also limited to one PDS unit and thus cannot be extrapolated to all the PDS units in Finland.…”
Section: Discussionmentioning
confidence: 62%
“…Household income is one of the major factors that determine the levels of ability to pay according to Widström and Seppälä [12]. Their study conducted in three large municipalities near Helsinki proved that clinical (dental) history and the urgency of the dental service were also factors of critical importance.…”
Section: Discussionmentioning
confidence: 99%